Engaging with Immigrant Adolescent Learners to Co-construct an Acculturation Strategy for Integration in South African Schools - Mabvira, Agrippa (University of the Witwatersrand, Johannesburg, 2023)
Immigrant adolescent learners have a dual task of acculturating into new society whilst adjusting to normative age-related psychological, social and biological developments. Hence, a theory-driven, and evidence-based acculturation strategy for integration is imperative in aiding immigrant adolescents as they navigate through the simultaneous occurrence of developmental milestones with acculturation related tasks. In this study, I aimed to explore the affordances and challenges faced by immigrant adolescent learners during their process of acculturation and use the findings to co-construct an acculturation strategy for integration. The paradigm of this intervention study is critical realism. The two theoretical frameworks that I used to underpin this study are the human capabilities approach and acculturation theory. This qualitative study used participatory action research, to ensure active involvement of twelve (12) immigrant adolescent learners as co-researchers. I used purposive sampling strategy to recruit participants from three public schools in the Mthatha Township, Eastern Cape Province, South Africa (SA). Data was collected through photovoice and focus group discussions. I then analysed the data using thematic data analysis which yielded a synthesis of affordances and challenges to acculturation. Findings of this study offered rich and thick descriptions of co-researchers’ perspectives on how to foster successful acculturation and integration. Main findings include that language proficiency is a key determinant factor of acculturation outcomes. Hence, co-researchers recommended language support and immersion programmes. Moreover, discrimination by peers, educators, and community members emerged as a major impediment to integration. To address the problem of discrimination, this study recommends a culturally responsive curriculum in schools, intercultural training for educators and awareness campaigns that should focus on attitudinal change for communities. Another significant output of this study are recommendations given to various stakeholders who are key to an acculturation strategy for the integration of immigrant adolescent learners in SA schools. Moreover, supported by critical realism, the study calls for broader multiculturalism and diversity education to facilitate the integration of immigrant adolescent learners.
Thesis submitted in fulfillment of the requirement for the degree of Doctor of Philosophy (PhD) in the Faculty of Humanities, in the School of Human and Community Development, in the Department of Social Work, at the University of Witwatersrand, Johannesburg, in 2023.
Keywords: Acculturation Strategy; Co-construct; Immigrant Adolescent; Integration; Mthatha Township, Eastern Cape Province, South Africa (SA); UCTD; SDG-4: Quality education